Hubungan Status Gizi dengan Kejadian Anemia pada Siswa Kelas X SMK Muhammadiyah 2 Bejen Bantul Yogyakarta - Sugiyanto Sugiyanto (STIKes Surya Global Yogyakarta, 2018)
Nutrition is one of determinant quality of human resources. Malnutrition will cause failure of physical growth and intellectual development, decrease productivity and immune system, which increases the morbidity and mortality. This Study was aimed to determine the correlation nutritional status with anemia event of students in class X SMK Muhammadiyah 2 Bejen Bantul Yogyakarta. The method used the analytic survey with cross sectional approach. The technique of data collection was using purposive sampling, sample used as many as 30 of students who have get anemic. The material and equipment which was used in this study including stationery, weight and height scales, electric appliance of Hb Measurement, alcohol cotton, handscon, and data analysis using non parametric statictical test with Kendall Tau. Based on non parametric statistic test using Kendall Tau test with significance level of 0.05 and p value (significance) of 0.000. In this study obtained p value (significance) was smaller than 0.05 (0.000 0.05) so that Ha is accepted. It can be concluded that there was a correlation of nutritional status with anemia event of students in class X SMK Muhammadiyah 2 Bejen Bantul Yogyakarta. It was hoped the students have to eat three times a day so that nutrition was fulfilled and not doing a wrong diet, so it has a good nutritional status and avoid anemia.